Production, Characterization, and Industrial Application of Pectinase Enzyme Isolated from Fungal Strains - Sudeep KC; Jitendra Upadhyaya; Dev Raj Joshi; Binod Lekhak; Dhiraj Kumar Chaudhary; Bhoj Raj Pant; Tirtha Raj Bajgai; Rajiv Dhital; Santosh Khanal; Niranjan Koirala; Vijaya Raghavan (Fermentation, 2020)
Pectinases are the group of enzymes that catalyze the degradation of pectic substances. It has wide applications in food industries for the production and clarification of wines and juices. The aim of this study was to isolate, screen and characterize pectinase from fungi isolated from various soil samples and evaluate its application in juice clarification. Fungal strains were isolated and screened primarily using 1% citruspectin incorporated potato dextrose agar (PDA) and secondarily using pectinase screening agar medium (PSAM) for pectinolytic organisms. The enzyme was produced by submerged state fermentation and assayed using the dinitro salicylic acid (DNS) method. From 20 different soil samples, 55 fungal isolates were screened primarily and, among them, only 14 isolates were subjected for secondary screening. Out of 14, only four strains showed the highest pectinolytic activity. Among four strains, Aspergillus spp. Gm showed the highest enzyme production at a 48-h incubation period, 1% substrate concentration, and 30 °C temperature. The thermal stability assessment resulted that the activity of pectinase enzyme declines by 50% within 10 min of heating at 60 °C. The optimum temperature, pH, and substrate concentration for the activity of enzyme was 30 °C (75.4 U/mL), 5.8 (72.3 U/mL), and 0.5% (112.0 U/mL), respectively. Furthermore, the yield of the orange juice, the total soluble solid (TSS), and clarity (% transmittance) was increased as the concentration of the pectinase increased, indicating its potential use in juice processing. Overall, the strain Aspergillus spp. Gm was identified as a potent strain for pectinase production in commercial scale.